Call sign Lightning : inside the rowdy world and risky missions of the Marines' elite ANGLICOs / Scott Messmore - Messmore, Scott
"The U.S. Marine Corps' Air Naval Gunfire Liaison Companies--usually referred to as ANGLICOs--are the unsung heroes of the U.S. military. Small squads of these marines are inserted deep behind enemy lines to identify targets and direct fire from aircraft, ground artillery, and naval guns. They are among the best of the best, and their radio call sign "Lightning" is recognized throughout the military as the gold standard of qualification and capability."